Deformation and Fracture Properties of the Soft Magnetic Composite Somaloy 700 3P on Different Length Scales - Schwark, Tabea Gisela (KIT Scientific Publishing, 2021)
Soft Magnetic Composites (SMCs) typically consist of large iron particles coated with a fairly thin inorganic layer. The combination of soft particles with a brittle layer causes, however, a rather poor mechanical behaviour of the SMCs. The particle boundaries of the specific SMC Somaloy 700 3P can be classified into four different types according to the complexity of their layers. Tests on both micro- and macroscale showed that the particle-boundary interface is critical in terms of failure.